PERBANDINGAN PERILAKU HARIAN JANTAN DAN BETINA BURUNG ELANG BONDOL (Haliastur indus Boddaert, 1783) DI TAMAN MARGASATWA RAGUNAN JAKARTA - Syari'ati, Esti; Sukandar, Paskal; Isfaeni, Hanum (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Brahminy Kite (Haliastur indus) is included in protected wild species list. Concervation is an alternative way to save this species from being extinct. The objective of this research was to find out the comparison of daily behaviour between male and female Brahminy Kite at Ragunan Zoo- Jakarta such as three activities. These behaviours were motionless, movement and ingestive. The descriptive method was used in this study, by direct observation to the behaviour of individual bird. The focal animal sampling was used as a method for recording behaviour, which means observing one individual for a specified amount of frequence and recording all instance of its behaviour. The observation was carried out on 2 birds with sex male and female. Each individual’s bird was observed each day from 06.00 to 18.00. Data analysis used descriptive analysis and nonparametric statistics analysis with U Mann-Whitney Test. The result of this analysis indicated if there were comparison of motionless behaviour and movement behaviour between male and female Brahminy Kite, where testing criteria Eject H , density is 0.00 < α, level was significance but there was not comparison of ingestive behaviour between male and female Brahminy Kite. Density is 0.38 > α,level was insignificant Keyword : the comparison, daily behaviour, Brahminy Kite, Ragunan zoo